Two new marine cyst genera from Upper Cretaceous Brookian megasequence strata in the North Slope of Alaska. (22nd December 2017) - Ravn, Robert L.; Goodman, David K.
ABSTRACT: Two new genera, comprising three new species, of marine algal cysts are described here. The extinction horizons of all three occur with a high degree of consistency in many petroleum wells in the Alaska North Slope region. These horizons provide useful correlation events within the overall progradational sediments which filled a large and complex depositional basin during Cenomanian–Turonian time. The newly described taxa are Paranelsoniella woodii gen. et sp. nov., P. minuta gen. et sp. nov. and Xanthocysta ovata gen. et sp. nov.